Factors Affecting Customer's Purchase Decision of Makeup Products From Local Brands On TikTok Live Streams - Prameswari, Tyara Zeta; Kusumawati, Nurrani (Integrasi Sains Media, 2024)
Social media platforms have drastically reshaped communication, content sharing, and consumption in the fast-evolving digital era. TikTok, a prominent platform, has gained substantial influence in Indonesia, becoming a significant force in the business world. This study examines the factors that affect consumer purchase decisions for local makeup products during TikTok live-streaming sessions. Utilizing a mixed-methods approach, the research integrates qualitative and quantitative methods to understand consumer behavior comprehensively. Qualitative data is analyzed through manual coding, offering detailed insights into consumer perceptions and motivations. Quantitative data is assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify statistical relationships and patterns. The study involves a minimum of 12 participants for qualitative analysis and 200 for quantitative analysis, focusing on beauty enthusiasts familiar with TikTok's live-streaming features. The research aims to uncover how live streaming influences purchasing decisions and provides actionable insights for local beauty brands. By leveraging TikTok's interactive capabilities, the findings will help these brands enhance their marketing strategies and engage more effectively with their target audience. This study contributes to understanding the impact of social media on consumer behavior and offers practical recommendations for maximizing the potential of live streaming in the beauty industry.